2009
DOI: 10.1590/s1678-77572009000500024
|View full text |Cite
|
Sign up to set email alerts
|

A scanning electron microscopic study of the patterns of external root resorption under different conditions

Abstract: Objective:The aim of this study was to examine if there are qualitative differences in the appearance of external root resorption patterns of primary teeth undergoing physiologic resorption and permanent teeth undergoing pathological root resorption in different conditions.Material and Methods:A total of 40 teeth undergoing external root resorption in different conditions were divided into 4 groups and prepared for examination under scanning electron microscopy at magnifications ranging from 20x to 1000x. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…[10] Studies have reported that root resorption in primary teeth depends on the germ of permanent successor as well as other factors. [1,[5][6][7][8] Furthermore, the morphological relationship between the roots of the primary teeth and the crowns of the permanent successors should be considered. [2] In this study, a situation in which the germ of the permanent successor completely occupied only one of the roots of the primary tooth was considered atypical resorption, which may explain the greater prevalence of asymmetrical root resorption in the primary molars of children aged 8-12 years, as primary molars undergo a natural exfoliation process in this period, in comparison to those aged 3-7 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Studies have reported that root resorption in primary teeth depends on the germ of permanent successor as well as other factors. [1,[5][6][7][8] Furthermore, the morphological relationship between the roots of the primary teeth and the crowns of the permanent successors should be considered. [2] In this study, a situation in which the germ of the permanent successor completely occupied only one of the roots of the primary tooth was considered atypical resorption, which may explain the greater prevalence of asymmetrical root resorption in the primary molars of children aged 8-12 years, as primary molars undergo a natural exfoliation process in this period, in comparison to those aged 3-7 years.…”
Section: Discussionmentioning
confidence: 99%
“…These situations of root resorption were associated with areas of periradicular bone rarefactions and tooth decay with pulp involvement, which is in agreement with fi ndings described in previous studies. [1,6,7] It is not possible to identify the initial moment of root resorption clinically or through radiographs. Only advanced stages of root resorption are seen in radiographic exams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the hard tissues of permanent teeth are not resorbed under healthy conditions and the resorption is thus considered a pathologic process [72]. Different causes have been attributed to the root resorption process including pressure, inflammation, neoplastic process and systemic conditions [73]; however, the biological phenomena underlying root resorption are still not completely understood. Tooth root resorption is regarded as a major problem encountered after tooth replantation and orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…Some works showed crater-like (Lomcali et al, 1996), funnel-like (Malueg et al, 1996;Sreeja et al, 2009), and irregular morphologies (Felippe et al, 2009). Some works showed crater-like (Lomcali et al, 1996), funnel-like (Malueg et al, 1996;Sreeja et al, 2009), and irregular morphologies (Felippe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%